Occurrence of Lead (Pb) Metal in Water, Sediment, and Bioaccumulation in Giant Mudskipper (Boleopthalmus : Gobiidae) from the Pemangkat Mangrove Area West Kalimantan - Sofiana, Mega Sari Juane; Safitri, Ikha; Nurhidayanti (Sam Ratulangi University, 2024)
Pemangkat is a coastal area in Sambas Regency which has a mangrove ecosystem. One of the biota found in mangrove forest areas is the Giant Mudskipper. This fish is often used as an environmental bioindicator due to its characteristics of living in the intertidal zone and being able to absorb and accumulate metals. Heavy metal pollution in marine and coastal areas has become a global problem that causes negative impacts on ecosystems, biota, and human health. One of the heavy metals that can pollute waters due to fishing and port activities is lead (Pb). Pemangkat is one of the centers of capture fisheries activities in West Kalimantan. Therefore, this research aims to analyze the content of the heavy metal of Pb in water, sediment, and Mudskipper in the Pemangkat mangrove ecosystem, Sambas, West Kalimantan. The Pb content in water, sediment, and Giant mud skipper samples was analyzed using an Atomic Absorption Spectrophotometer (AAS) at a wavelength of 283.3 nm. Accumulation of heavy metal in the biota was determined by the bioconcentration factor (BCF). The concentration of lead metal (Pb) in water and sediment samples was highest at Station II, such as 0.40 mg/L and 0.25 mg/L respectively. The metal content of Pb in Giant Mudskipper was highest at Station I (0.224 mg/kg). The BCF values for Giant Mudskipper at Stations I and II were 1.18 and 0.86. Keywords: Lead (Pb), Mangrove, Mudskipper, Boleopthalmus. Abstrak Pemangkat merupakan wilayah pesisir di Kabupaten Sambas yang memiliki ekosistem mangrove. Salah satu biota yang hanya ditemukan di daerah hutan mangrove adalah ikan tembakul. Ikan ini sering dijadikan bioindikator lingkungan dikarenakan karakteristiknya yang hidup di zona intertidal yang mampu menyerap dan mengakumulasi logam. Pencemaran logam berat di wilayah laut dan pesisir telah menjadi permasalahan global yang menyebabkan dampak negatif bagi ekosistem, biota, dan kesehatan manusia. Salah satu logam berat yang dapat mencemari perairan dengan adanya aktivitas perikanan dan pelabuhan adalah logam Pb. Pemangkat adalah salah satu sentra kegiatan perikanan tangkap di Kalimantan Barat. Oleh karena itu, penelitian ini bertujuan untuk menganalisis kandungan logam berat Pb di air, sedimen, dan ikan tembakul di ekosistem mangrove Pemangkat, Sambas, Kalimantan Barat. Kandungan Pb di sampel air, sedimen dan ikan tembakul dianalisis dengan menggunakan Spektrofotometer Serapan Atom (SSA) pada panjang gelombang 283,3 nm. Akumulasi logam berat pada biota ikan tembakul ditentukan dengan faktor biokonsentrasi (BCF). Konsentrasi logam timbal (Pb) pada sampel air dan sedimen tertinggi pada Stasiun II, yaitu: 0,40 mg/L dan 0,25 mg/L secara berurutan. Kandungan logam Pb pada ikan tembakul tertinggi pada Stasiun I, yaitu 0,224 mg/kg. Nilai BCF ikan tembakul di Stasiun I dan II adalah 1,18 dan 0,86. Kata kunci: Timbal (Pb), Mangrove, Tembakul, Boleopthalmus